THE STIMULATION OF ELEMENTARY SCHOOL STUDENTS’ SOCIAL-EMOTIONAL DEVELOPMENT THROUGH YOGA ASANAS - Kadek Aria Prima Dewi PF (IAHN-TP Palangka Raya, 2019)
This study aimed to describe the process of elementary school students’ social-emotional development through Yoga Asanas. Social and emotional intelligence plays an important role in determining one's success (Daniel Goleman in Iriyanto, 2006). This intelligence can encourage the development of children to start and have social relationships with others and become the basis for the development of their academic ability. This research was focused on elementary school students especially in big classes (class IV-VI). Yoga Asanas was an option to stimulate social-emotional intelligence because there were movements that could stimulate that ability through body movement exercises which corresponded to the growth and development of the brain in the secondary phase of Yoga Asanas.